ANALISIS SAFE BEHAVIOR DENGAN PENDEKATAN BEHAVIOR-BASED SAFETY PADA RADIOGRAFER DI RUMAH SAKIT Dr. SOETOMO SURABAYA - Neni Rahmawati (The Indonesian Journal of Occupational Safety and Health, 2017)
The development of science in health world may let use radiation to diagnose a disease. Radiation have some bad effect if excessively exposed, so that management should be create radiographer’s safe behavior to prevent an accident. Management could applied behavior based safety  with a behavioral intervention effort and external factor to encourage radiographer’s safe behavior. The aim of this research was to analyze safe behavior by using behavior based safety approach for radiographer in Instalasi Radiodiagnostik Rumah Sakit Dr. Soetomo Surabaya. This was a cross sectional study with qualitative approach in order to know about behavioral intervention effort and external factor in Instalasi Radiodiagnostik Rumah Sakit Dr. Soetomo Surabaya. Respondent of this research was 11 people who all authorized as radiographer in Instalasi Radiodiagnostik Rumah Sakit Dr. Soetomo Surabaya. The results of this research represent that radiographer’s behavior in Instalasi Radiodiagnostik Rumah Sakit Dr. Soetomo Surabaya 100% included in safe category. Management has used behavioral intervention effort properly, by applied activator and consequence to direct and motivate radiographer’s behavior. As discovered that the external factor of instalasi radiodiagnostik has support radiographer to perform safe behavior. The conclusion of this research was radiographer’s safe behavior created by behavioral intervention effort which used activator and consequence to direct and motivate radiographer’s safe behavior and external factor supporting radiographer’s safe behavior in Instalasi Radiodiagnostik Rumah Sakit Dr. Soetomo Surabaya. Keywords: behavioral intervention effort, external factor, safe behavior